(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
This article discusses the issue of career choice and its socio-psychological significance, the selection of criteria for the career selection system, factors influencing career choice, and the issues of guiding students to a career and teaching them to freely choose a career. . Also, the article examines the scientific-theoretical and practical-methodological aspects of the selection of the criteria of the attitude factor to the choice of profession, as well as the aspects of their research